Lubuskie Sejmiki Kultury województwa zielonogórskiego w latach 1957-1992 na łamach "Gazety Zielonogórskiej"/"Gazety Lubuskiej" = Lubusz Culture Assemblies (Lubuskie Sejmiki Kultury) in the Zielona Góra region in the years 1957-1992 in "Gazeta Zielonogórska/"Gazeta Lubuska" - Korniluk, Izabela (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The article raises the issue of representation in the daily press of the work and activities of the Lubusz Cultural Society (Lubuskie Towarzystwo Kultury). It examines the processes occurring in this daily newspaper through which the journalists presented and interpreted the schematically organized, and pre-prepared meetings of cultural activists in the form of culture assemblies, which took place every 4 years in Zielona Góra.
Keywords: prasa; prasa codzienna; Lubuskie Towarzystwo Kultury; działacze kulturalno-oświatowi; press; daily press; Lubusz Cultural Society; cultural and educational activists